Birdwatching, Ornitological Tourism and Avitourism: Terminological Dispute and Review of World and Russian Practices - Afanasiev, Oleg (Anais Brasileiros de Estudos Turísticos, 2022)
Nature-oriented types of tourism in the current conditions are particularly relevant. Today, destinations offering an ecotourism tourism product are in demand. Birdwatching, an integral part of ecotourism programs, is especially popular in the countries of North America and Western Europe. In Russia, activity associated with watching birds is gaining popularity. Birdwatching has several advantages due to almost any territory is inhabited by birds, and therefore it is possible to organize observations for them. However, there are many terminological blank spots and problems. That is why the article is aimed at substantiating and characterizing the modern forms of birdwatching and ornithological tourism and confirming them by studying practices of organizing observations of the avifauna. The article provides a review of scientific publications dedicated to birdwatching. Today there is an abundance of terms denoting the observation of birds in their natural environment: birding, birdwatching, twitching, ornithological tourism, avitourism. The study of cases and theoretical works makes it possible to characterize each of these concepts and distinguish between them. Today, there is a growing trend in the popularity of urban birding and avitourism, in which the natural habitat is the urbanized environment. Observations of the avifauna can also be organized in marginalized territories, and this makes it possible to consider them as places for ecotourism. The research result is important methodological conclusion about the relationship among the concepts of birdwatching, ornithological tourism and avitourism.